The Khazars : A Judeo-Turkish Empire on the Steppes, 7th–11th Centuries AD /: A Judeo-Turkish Empire on the Steppes, 7th–11th Centuries AD. (2019) - Zhirohov, Mikhail; Nicolle, David
No abstract available